TRANSFORMAREA PROFESIEI BIBLIOTECARE (TRADUCERE DE LIDIA KULIKOVSKI) - FELDMAN, Sari; RICH, Hallie (BIBLIOPOLIS, 2020)
The technological advancements are driving an increasingly interconnected global landscape, which contributes to rapid political, economic, social, and environmental change. Faster communication systems and enhanced access to information bind countries, economies, and businesses in far more complex ways than we have ever conceived. This interdependence on a global scale makes risks such as rising socioeconomic inequality particularly pernicious because of the inherent instability of weak economies and social fragility. In order to be effective in this evolving global landscape, library organizations must be nimble, creative, and customer-focused, and—above all—must embrace learning. Gone are the days when libraries cornered the market on information, delivering value almost exclusively as content providers. Library work creates value today in ways that are far more personal and collaborative. Library professionals need to be viewed as trusted advisors, but trust grows only when we build relationships with our customers.